AKTULALISASI PEMBELAJARANBERPUSAT PADA SISWA SMA DJ KABUPATENKLATEN
The objective of this research is to evaluate of the quality of international standard schools (in Indonesia called SB/) and national standard schools (SSN) of senior high schools compared to other senior high schools categorized as neither SBI nor SSN located in’Klaten. The evaluation focused on goal-oriented evaluation of the two issues: (1) teachers’ attempts to deal with student-centred teaching and learning activities and .(2) teachers’ attempts to encourage their students to learn. This research was conducted at SMAN 1 Klaten (SB1), SMA 2 Klaten (SSN),SMAN Jogart lan andSMAN Prambanan, which is neither SBI nor SSN. To obt in the data, two sets of questionnaires were administered.’To triangulate and to slipport data collection, interviews with,the principals of, the four schools were cOl